Anthropological and fitness status of Croatian judoists - Sertic, H.; Segedi, I.; Milanovic, D. (Archives of Budo, 2006)
Study aim: To assess databases of anthropological and fitness characteristics of Croatian judoists available at the Croatian Judo Federation. Material/methods: Six male and 8 female elite judoists, and a group of 17 male junior judoists were subjected to anthropometric measurements and fitness (motor and functional) tests, the latter group being examined twice, at the age of 11 and 14 years. Results: Three databases were overviewed: the most informative, designed at the Sports Diagnostic Centre of Zagreb University, another one developed in a research project "Follow-up of the changes in anthropological status of children aged 11-14 years in wrestling sports", and a field tests set up by the Expert Coaching Committee of the Croatian Judo Association. So far, only few Croatian judoists pass all test procedures but effort is made to expand the programme and to include all age and weight groups of Croatian judoists. Conclusions: Regular examinations of athletes with the use of those databases should improve Croatian judo results thus reducing the gap between the Croatian and world judo achievements.